Does teal suit everyone? Psychosocial factors affecting work attractiveness in an organisation with a horizontal structure - Pawlak, Justyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
As success in today’s world is increasingly associated with an approach based on flexibility, decentralised control and quick response to the changing conditions, a new approach to the functioning of organisations is needed. Previous guidelines influencing the way many companies operate, which were based on hierarchy, competition and maximising profits, have ceased to respond to changes taking place in the world. An additional important variable is the change in the labour market and employees’ expectations, therefore, recruitment, increasing commitment and retention in the organisation have all become more of a challenge for managers. One of the possible responses to these changing conditions is the creation of horizontal organisations, such as teal (turquoise) ones. However, as some organisations based on this model achieve success, while others return to traditional solutions, attention should be paid to factors affecting the satisfaction and effectiveness of employees’ work in this type of organisations. Based on literature analysis and a case study, the paper discusses psychosocial determinants of work in a teal organisation, related, among others, to the changing approach to work by younger generations, different needs of employees, changes in the education system, as well as to personality predispositions. Recognition of these factors may be helpful in planning recruitment, considering the possibility of implementing teal solutions in a particular organisation, and may also help to include this option in the analysis of individual predispositions in the process of career guidance.

W związku z szybko zachodzącymi zmianami we współczesnym świecie dotychczasowe zasady kształtujące sposób funkcjonowania wielu firm, które w dużym stopniu opierały się na hierarchii, konkurencji i maksymalizacji zysków, stają się coraz mniej aktualne. Sukces natomiast znacznie częściej wiąże się z podejściem opartym na elastyczności, zdecentralizowanej kontroli i szybkim reagowaniu na zmieniające się warunki. Dodatkowo nastąpiła zmiana w oczekiwaniach pracowników, dlatego też rekrutacja, zwiększanie zaangażowania i retencja pracowników stały się jednym z ważniejszych wyzwań dla menedżerów. Jedną z możliwych odpowiedzi na zmieniające się warunki jest tworzenie organizacji o horyzontalnej strukturze, np. turkusowych. Ponieważ jednak niektóre organizacje, które opierają się na tym modelu, osiągają sukces, podczas gdy inne wracają do tradycyjnych rozwiązań, należy zwrócić uwagę m.in. na czynniki wpływające na satysfakcję i efektywność pracowników w tego typu organizacjach. W artykule, w oparciu o analizę literatury i case study, omówiono psychospołeczne determinanty pracy w organizacji turkusowej, związane m.in. ze zmieniającym się podejściem do pracy młodego pokolenia, odmiennymi potrzebami pracowników, zmianami w systemie edukacji, a także predyspozycjami osobowościowymi. Rozpoznanie tych czynników może być pomocne w planowaniu rekrutacji, rozważeniu możliwości wdrożenia turkusowych rozwiązań w danej organizacji, a także może pomóc w uwzględnieniu tej opcji w analizie indywidualnych predyspozycji w procesie doradztwa zawodowego.
Keywords: teal organisation; turquoise organisation; job satisfaction; employees’ needs; organisational commitment; organizacja horyzontalna; organizacja turkusowa; satysfakcja z pracy; potrzeby pracowników; zaangażowanie organizacyjne